2006
DOI: 10.1162/089892906775250094
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Expertise Effects Are Not All or None: Spatially Limited Perceptual Expertise for Faces in a Case of Prosopagnosia

Abstract: Abstract& We document a seemingly unique case of severe prosopagnosia, L. R., who suffered damage to his anterior and inferior right temporal lobe as a result of a motor vehicle accident. We systematically investigated each of three factors associated with expert face recognition: fine-level discrimination, holistic processing, and configural processing (Experi-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
69
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 53 publications
9
69
0
Order By: Relevance
“…They also sustain the idea that lesions to the ILF can cause prosopagnosia by disconnecting core face areas from the anterior temporal lobes (Yamasaki et al, 2004;Lanyon et al, 2009). The latter are also necessary for face recognition (Barton et al, 2002;Bukach et al, 2006;Gainotti, 2007). Only the ventral and medial segments of the ILF (connected to inferior/middle temporal gyri, and the medial temporal lobe respectively) were damaged in FE, which suggests that the surviving dorsal segment (connected to the superior temporal gyrus) is not sufficient for overt recognition.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…They also sustain the idea that lesions to the ILF can cause prosopagnosia by disconnecting core face areas from the anterior temporal lobes (Yamasaki et al, 2004;Lanyon et al, 2009). The latter are also necessary for face recognition (Barton et al, 2002;Bukach et al, 2006;Gainotti, 2007). Only the ventral and medial segments of the ILF (connected to inferior/middle temporal gyri, and the medial temporal lobe respectively) were damaged in FE, which suggests that the surviving dorsal segment (connected to the superior temporal gyrus) is not sufficient for overt recognition.…”
Section: Discussionsupporting
confidence: 58%
“…Previous fMRI work has clearly shown that damage to either core area, OFA or FFA, produces AP (Sergent and Signoret, 1992a;Barton et al, 2002;Marotta et al, 2001;Hadjikhani and de Gelder, 2002;Rossion, 2008;Sorger et al, 2007;Steeves et al, 2006). These areas are thought to feed into the anterior inferior temporal cortex -henceforth the fusiformtemporal pathway (Rossion, 2008), that when damaged also results in failed face recognition (Barton et al, 2002;Bukach et al, 2006;Gainotti, 2007). The consequences of disrupting either the core or the extended face systems for unconscious face recognition are still uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, prosopagnosic patients present a lack of sensitivity to eye information for both familiar and unfamiliar face recognition (Bukach, Bub, Gauthier, & Tarr, 2006;Bukach, Le Grand, Kaiser, Bub, & Tanaka, 2008;Caldara et al, 2005;Rossion, Kaiser, Bub, & Tanaka, 2009), despite a normal sensitivity to the mouth area; these obhighest spatial frequency band, the left eye and the nose/ mouth area in the second highest spatial frequency band, all inner features in the mid spatial frequency band, and, finally, the eyes/nose area in the second lowest frequency band. One obvious difference between the results of these two studies and the results of our study is the statistical significance or lack thereof of the mouth in the two highest frequency bands.…”
Section: Resultsmentioning
confidence: 99%
“…Typical susceptibility to the original matching procedure was reported in patient Herschel, who developed AP following extensive lesions predominantly in the right occipitotemporal cortex (Rezlescu, Pitcher, & Duchaine, 2012). When tested using the complete design, patient LR, an individual who developed AP following focal damage to the anterior portion of the right temporal lobe, exhibited a typical composite effect (Bukach, Bub, Gauthier, & Tarr, 2006). However, this result is qualified by an abnormal pattern of responses; specifically, the time taken by LR to identify the top half of the face was influenced by the bottom half in both the aligned and misaligned conditions, indicative of an atypical composite effect (Busigny et al, 2014).…”
Section: Brain Stimulation and Neuropsychologymentioning
confidence: 90%